THE INFLUENCE OF TRUST AND SERVICE QUALITY ON CONSUMER LOYALTY THROUGH LAZADA APPLICATION USERS: PENGARUH KEPERCAYAAN DAN KUALITAS LAYANAN TERHADAP LOYALITAS KONSUMEN MELALUI PENGGUNA APLIKASI LAZADA - Kristiani Halawa, Nofi (LPPM UPMI, 2024)
The aim of this research is to test and analyze the influence of trust and service quality on consumer loyalty among Lazada application users. This research seeks to find out how trust and service quality influence consumer loyalty for Lazada mobile application users. By understanding the relationship between these variables, companies can know and identify what needs to be improved and what strategies need to be implemented to increase consumer loyalty. The research method carried out by the researcher is the literature method, which means that this research is qualitative research with descriptive analysis techniques of library research (library search) where this research is focused on describing existing phenomena. The results of this research are that the trust variable has a positive and significant effect on consumer loyalty. Lazada application users who feel confident in the platform, especially in terms of transaction security and information reliability, tend to be more loyal and continue to use the application for online shopping. The service quality variable has a partial and significant effect on consumer loyalty. Service quality that includes reliability, responsiveness, assurance and empathy has been proven to increase consumer satisfaction, which then strengthens their loyalty. The variables of trust and service quality simultaneously and partially influence consumer loyalty.